2013
DOI: 10.1016/j.bbmt.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of Mitochondrial DNA Minisatellites after Stem Cell Transplantation

Abstract: Mitochondrial DNA has been used to investigate phylogenetic relationships and pathophysiologic roles in aging, degenerative diseases, and cancer. We investigated the prognostic usefulness of mitochondrial DNA minisatellite (mtMS) markers compared with nuclear short tandem repeat markers by evaluating the laboratory performance and clinical value of these markers in a large sample of patients undergoing allogeneic hematopoietic stem cell transplantation (allo-HSCT) with various simulated conditions in vitro and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…This is attributed to the hematopoiesis of the recipient's native CD34+ derived cells despite the cytoreductive treatment prior to the allograft transplant. Several studies have shown strong positive correlation between the extent of mixed chimerism and the likelihood of patient hematologic relapse [4,[6][7][8][9]. The magnitude of mixed chimerism is frequently measured using PCR-based methods [10,11] as a ratio of the recipient genotype signal to that of the donor.…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to the hematopoiesis of the recipient's native CD34+ derived cells despite the cytoreductive treatment prior to the allograft transplant. Several studies have shown strong positive correlation between the extent of mixed chimerism and the likelihood of patient hematologic relapse [4,[6][7][8][9]. The magnitude of mixed chimerism is frequently measured using PCR-based methods [10,11] as a ratio of the recipient genotype signal to that of the donor.…”
Section: Introductionmentioning
confidence: 99%